PEREMPUAN DAN MODERNISASI WOMEN AND MODERNIZATION - Thung, Ju Lan (P2KK LIPI, 2015)
In this article, the writer discusses different kind of changes experienced by women in rural and urban areas due to the process of modernization. But in general they both experience a shift in values about family and working outside their home. Nevertheless, modernization does not bring gender equality as it promises. The fact even shows a clear social and cultural gap between women themselves, particularly between those living in rural and urban areas. The shift in values as well as changes in gender relations do not solve women’s problems and dilemma, especially those of poor village women. Therefore, it is important to rethinking the State policies which at the present have been focused on the intensification of the women’s role in development. It is imperative to pay attention to the role of women in the family as the main pillar for nation and society progress. Keywords: women, modernization, gender equality, rural and urban women